2022
DOI: 10.3390/ijerph19159289
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Environmental Dynamism on Chinese Tour Guides’ Sustainable Performance: Factors Related to Vitality, Positive Stress Mindset and Supportive Policy

Abstract: Although previous research shows great interest in improving the sustainability of organizations’ performance, little is known about individual sustainable performance, especially for special groups such as tour guides. Drawing on the Conservation of Resources (COR) theory, this study aimed to investigate the effect of environmental dynamism caused by COVID-19 on tour guides’ sustainable performance and mediating role of vitality and intervention mechanism in this relationship. Adopting a quantitative research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Tourism studies increasingly recognize the significance of synthesizing TGs' performance (Doyle and Kelliher, 2023; Huang et al , 2010; Sun et al , 2022; Syakier and Hanafiah, 2022; Zhang and Chow, 2004), with a recent line of enquiry approaching the construct through the lens of EI theories (Gültekin and Icigen, 2019; Min, 2017; Min and Peng, 2012; Tekeli and Özkoç, 2022; Tsaur and Ku, 2019). Even though the relations between EI and TGs' performance are reportedly considered crucial, there has been a lack of past research studies on the effects of EI on TGs' performance with special reference to the citizenship behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tourism studies increasingly recognize the significance of synthesizing TGs' performance (Doyle and Kelliher, 2023; Huang et al , 2010; Sun et al , 2022; Syakier and Hanafiah, 2022; Zhang and Chow, 2004), with a recent line of enquiry approaching the construct through the lens of EI theories (Gültekin and Icigen, 2019; Min, 2017; Min and Peng, 2012; Tekeli and Özkoç, 2022; Tsaur and Ku, 2019). Even though the relations between EI and TGs' performance are reportedly considered crucial, there has been a lack of past research studies on the effects of EI on TGs' performance with special reference to the citizenship behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Okaily (2022) further found that TGs' citizenship performance includes five key dimensions: (1) Helping, which captures TGs' pro-social acts toward tourism society, such as co-workers; (2) Self-development, which relates to TGs' capacity to expand their professional knowledge and skills with time; (3) Initiative, which explains proactive efforts on the part of TGs, such as handling anticipated obstacles during a tour; (4) Compliance, which demonstrates TGs' commitment to follow work regulations without formal monitoring and (5) Adaptability, which concerns TGs' social and physical coping abilities. However, additional studies in TG performance have informally included factors related to citizenship behaviors (Cetin and Yarcan, 2017; Huang et al , 2010; Sun et al , 2022; Syakier and Hanafiah, 2022). For instance, Zhang and Chow (2004) examined TGs' performance in Hong Kong through factors like helping, initiative and compliance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 To our knowledge, there was no prior research analyzing the mechanism effect between tour guides’ working status and psychological status in the context of COVID-19. At present, this theory mainly focuses on the study of tour guide’s job satisfaction 48 and sustainable performance, 49 but neglects the study of tour guide’s negative mental state. This study attempted to fill this gap.…”
Section: Discussionmentioning
confidence: 99%